Sum 1

Calculus Level 4

Let the sequence { a n } \left\{a_n\right\} be defined as a n = 2 n n + 1 ( n = 0 , 1 , 2 , 3 , . . . ) a_n=\frac{2^n}{n+1} \quad (n=0, 1, 2, 3, ...) and let b n b_n be the sequence of partial sums of a n a_n : b n = k = 0 n a k . b_n=\sum_{k=0}^n {a_k}. Evaluate n = 1 ( b n 1 n 2 n ) . \sum_{n=1}^\infty {\left(\frac{b_{n-1}}{n\cdot2^n}\right)}. If the answer is of the form π r s \dfrac{\pi^r}{s} , where r r and s s are both positive integers, find r + s r+ s .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Anton Wu
Jun 6, 2017

This is a solution that requires no knowledge of special functions.

Define the function F ( x ) F(x) : F ( x ) : = n = 1 ( 1 n ( 1 2 ) n b n 1 ( x 1 ) n ) F(x):=\sum_{n=1}^\infty {\left(\frac{1}{n} {\left(-\frac{1}{2}\right)}^n b_{n-1} {\left(x-1\right)}^n\right)} Note that F ( 1 ) = 0 F(1)=0 and F ( 0 ) F(0) is the answer to the problem.

The presence of the 1 n ( x 1 ) n \dfrac{1}{n} {\left(x-1\right)}^n term inspires us to take the derivative of F ( x ) F(x) : F ( x ) = n = 1 ( ( 1 2 ) n b n 1 ( x 1 ) n 1 ) = n = 0 ( ( 1 2 ) n + 1 b n ( x 1 ) n ) = 1 2 n = 0 ( ( 1 ) n 2 n b n ( x 1 ) n ) = 1 2 n = 0 ( ( 1 ) n 2 n k = 0 n ( 2 k k + 1 ) ( x 1 ) n ) = 1 2 n = 0 k = 0 n ( ( 1 ) n 2 n k ( k + 1 ) ( x 1 ) n ) = 1 2 n = 0 k = 0 n ( ( 1 ) k ( 1 ) n k 2 n k ( k + 1 ) ( x 1 ) k ( x 1 ) n k ) = 1 2 n = 0 k = 0 n ( ( 1 ) k k + 1 ( x 1 ) k ( 1 ) n k 2 n k ( x 1 ) n k ) = 1 2 k = 0 n = k ( ( 1 ) k k + 1 ( x 1 ) k ( 1 ) n k 2 n k ( x 1 ) n k ) = 1 2 k = 0 n = 0 ( ( 1 ) k k + 1 ( x 1 ) k ( 1 ) n 2 n ( x 1 ) n ) = 1 2 k = 0 ( ( 1 ) k k + 1 ( x 1 ) k ) n = 0 ( ( 1 ) n 2 n ( x 1 ) n ) = 1 2 ( ln ( 1 + ( x 1 ) ) x 1 ) ( 1 1 ( x 1 2 ) ) = ln x x 2 1 \begin{aligned} F'(x) &=\sum_{n=1}^\infty {\left({\left(-\frac{1}{2}\right)}^n b_{n-1} {\left(x-1\right)}^{n-1}\right)} \\ &=\sum_{n=0}^\infty {\left({\left(-\frac{1}{2}\right)}^{n+1} b_n {\left(x-1\right)}^n\right)} \\ &=-\frac{1}{2} \sum_{n=0}^\infty {\left(\frac{{\left(-1\right)}^n}{2^n} b_n {\left(x-1\right)}^n\right)} \\ &=-\frac{1}{2} \sum_{n=0}^\infty {\left(\frac{{\left(-1\right)}^n}{2^n} \sum_{k=0}^n {\left(\frac{2^k}{k+1}\right)} {\left(x-1\right)}^n\right)} \\ &=-\frac{1}{2} \sum_{n=0}^\infty {\sum_{k=0}^n {\left(\frac{{\left(-1\right)}^n}{2^{n-k}\left(k+1\right)}{\left(x-1\right)}^n\right)}} \\ &=-\frac{1}{2} \sum_{n=0}^\infty {\sum_{k=0}^n {\left(\frac{{\left(-1\right)}^k {\left(-1\right)}^{n-k}}{2^{n-k}\left(k+1\right)}{\left(x-1\right)}^k{\left(x-1\right)}^{n-k}\right)}} \\ &=-\frac{1}{2} \sum_{n=0}^\infty {\sum_{k=0}^n {\left(\frac{{\left(-1\right)}^k}{k+1}{\left(x-1\right)}^k \cdot \frac{{\left(-1\right)}^{n-k}}{2^{n-k}}{\left(x-1\right)}^{n-k}\right)}} \\ &=-\frac{1}{2} \sum_{k=0}^\infty {\sum_{n=k}^\infty {\left(\frac{{\left(-1\right)}^k}{k+1}{\left(x-1\right)}^k \cdot \frac{{\left(-1\right)}^{n-k}}{2^{n-k}}{\left(x-1\right)}^{n-k}\right)}} \\ &=-\frac{1}{2} \sum_{k=0}^\infty {\sum_{n=0}^\infty {\left(\frac{{\left(-1\right)}^k}{k+1}{\left(x-1\right)}^k \cdot \frac{{\left(-1\right)}^n}{2^n}{\left(x-1\right)}^n\right)}} \\ &=-\frac{1}{2} \sum_{k=0}^\infty {\left(\frac{{\left(-1\right)}^k}{k+1}{\left(x-1\right)}^k\right)} \sum_{n=0}^\infty {\left(\frac{{\left(-1\right)}^n}{2^n}{\left(x-1\right)}^n\right)} \\ &=-\frac{1}{2} \left(\frac{\ln{\left(1+\left(x-1\right)\right)}}{x-1}\right) \left(\frac{1}{1-\left(-\frac{x-1}{2}\right)}\right) \\ &=-\frac{\ln{x}}{x^2-1} \end{aligned} From here, it is possible to use the dilogarithm function to finish off the problem, but to solve it without knowledge of that function, we can recognize ln x x 2 1 -\dfrac{\ln{x}}{x^2-1} in integral form: F ( x ) = ln x x 2 1 = 0 ( y ( 1 + y 2 ) ( 1 + x 2 y 2 ) d y ) F'(x) = -\frac{\ln{x}}{x^2-1} = -\int_0^\infty {\left(\frac{y}{\left(1+y^2\right)\left(1+x^2y^2\right)}\,dy\right)} Integrating both sides with respect to x x , including the constant of integration C C : F ( x ) = 0 ( tan 1 ( x y ) 1 + y 2 d y ) + C F(x)=-\int_0^\infty {\left(\frac{\tan^{-1}{\left(xy\right)}}{1+y^2}\,dy\right)}+C Recall that F ( 1 ) = 0 F(1)=0 : F ( 1 ) = 0 ( tan 1 y 1 + y 2 d y ) + C = ( ( tan 1 y ) 2 2 ) 0 + C = ( ( ( π 2 ) 2 2 ) ( 0 2 2 ) ) + C = π 2 8 + C F(1)=-\int_0^\infty {\left(\frac{\tan^{-1}{y}}{1+y^2}\,dy\right)}+C=-{\left.\left(\frac{{\left(\tan^{-1}{y}\right)}^2}{2}\right)\right\rvert}_0^\infty+C=-\left(\left(\frac{{\left(\frac{\pi}{2}\right)}^2}{2}\right)-\left(\frac{0^2}{2}\right)\right)+C=-\frac{\pi^2}{8}+C Thus, C = π 2 8 C = \dfrac{\pi^2}{8} , so: F ( x ) = π 2 8 0 ( tan 1 ( x y ) 1 + y 2 d y ) F(x)=\frac{\pi^2}{8}-\int_0^\infty {\left(\frac{\tan^{-1}{\left(xy\right)}}{1+y^2}\,dy\right)} and we have: F ( 0 ) = π 2 8 0 ( 0 1 + y 2 d y ) = π 2 8 F(0)=\frac{\pi^2}{8}-\int_0^\infty {\left(\frac{0}{1+y^2}\,dy\right)}=\frac{\pi^2}{8} In summary, we have found that the sum is: n = 1 ( b n 1 n 2 n ) = F ( 0 ) = π 2 8 \sum_{n=1}^\infty {\left(\frac{b_{n-1}}{n\cdot2^n}\right)}=F(0)=\boxed{\dfrac{\pi^2}{8}} and the answer is 2 + 8 = 10 2+8=10 .

Aareyan Manzoor
Jun 23, 2017

define B ( x ) = 1 2 k = 1 n + 1 x k k B ( x ) = 1 2 k = 1 n + 1 x k 1 = x n + 1 1 2 ( x 1 ) B ( 2 ) = 1 2 0 2 x n + 1 1 x 1 d x B (x)= \dfrac{1}{2} \sum_{k=1}^{n+1} \dfrac{x^k}{k} \to B'(x)=\dfrac{1}{2}\sum_{k=1}^{n+1} x^{k-1}=\dfrac{x^{n+1}-1}{2(x-1)}\\ B(2)= \dfrac{1}{2} \int_0^2 \dfrac{x^{n+1}-1}{x-1} dx note B ( 2 ) B(2) is the partial sum asked in the question,i.e, b n b_n . the summation asked is then simply 1 2 n = 1 1 n . 2 n 0 2 x n 1 x 1 d x = 1 2 0 2 1 x 1 n = 1 ( ( x / 2 ) n n 1 n . 2 n ) d x = 1 2 0 2 ln ( 1 x / 2 ) + ln ( 1 / 2 ) x 1 d x = 1 2 0 2 ln ( 2 x ) 1 x d x \dfrac{1}{2}\sum_{n=1}^{\infty} \dfrac{1}{n.2^n}\int_0^2 \dfrac{x^{n}-1}{x-1} dx=\dfrac{1}{2}\int_0^2\dfrac{1}{x-1}\sum_{n=1}^{\infty} \left(\dfrac{(x/2)^n}{n}-\dfrac{1}{n.2^n}\right)dx\\=\dfrac{1}{2}\int_0^2\dfrac{-\ln(1-x/2)+\ln(1/2)}{x-1}dx=\dfrac{1}{2}\int_0^2\dfrac{\ln(2-x)}{1-x}dx substituting u = x 1 u=x-1 we have 1 2 1 1 ln ( 1 u ) u d u = 1 2 ( l i 2 ( 1 ) l i 2 ( 1 ) ) = π 2 8 \dfrac{1}{2}\int_{-1}^1\dfrac{\ln(1-u)}{-u}du=\dfrac{1}{2}(li_2(1)-li_2(-1))=\dfrac{\pi^2}{8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...